1988
DOI: 10.1143/jjap.27.l1623
|View full text |Cite
|
Sign up to set email alerts
|

Cation Ordering in LaBa2Cu2TaO8+y

Abstract: LaBa2Cu2TaO8+y crystallizes in a tetragonal unit cell with the dimensions a=3.9674(2) and c=12.052(1) Å, showing semiconductivity. In this compound, the Ta ions were found to preferentially occupy the Cu1 site between the two Ba layers in the LaBa2Cu3O7-y -type structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…͑They obtained NbO 2 layers.͒ The expectation, based on a cuprate-plane picture of superconductivity, was that R122M -8 would superconduct, but it did not ͑for either M ϭNb or M ϭTa). 6,101,102 It appears to us that the reason the R122Nb-8 compounds were expected to superconduct with higher critical temperatures than R123-7 was that Nb was perhaps expected to display a charge-state of ϩ3, rather than ϩ5. Our analyses of the bond-lengths in these compounds in terms of bondvalence-sum charges, indicate that the Nb charge-state is invariably ϩ5.…”
Section: B R122m-8mentioning
confidence: 99%
“…͑They obtained NbO 2 layers.͒ The expectation, based on a cuprate-plane picture of superconductivity, was that R122M -8 would superconduct, but it did not ͑for either M ϭNb or M ϭTa). 6,101,102 It appears to us that the reason the R122Nb-8 compounds were expected to superconduct with higher critical temperatures than R123-7 was that Nb was perhaps expected to display a charge-state of ϩ3, rather than ϩ5. Our analyses of the bond-lengths in these compounds in terms of bondvalence-sum charges, indicate that the Nb charge-state is invariably ϩ5.…”
Section: B R122m-8mentioning
confidence: 99%
“…3.1. XRD characterization of the samples X-ray powder diffractograms indicated that the prepared samples Sr2NdTaCu2Os, Sr2SmTaCu2Os, Sr2EuTaCu208 and SrzGdTaCuzOs were isostructural with tetragonal BazLaTaCu208 prepared by Murayama et al (1988). The unit-cell parameters were determined using the method proposed by Toraya (1993) by means of the computer program UNITCELL.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, A1 and Ni tend to occupy site (1) while Zn prefers site (2) (Jones et al, 1988). A complete replacement of square-planar-coordinated Cu ions by octahedrally coordinated Ta ions has been reported for © 1996 International Union of Crystallography Printed in Great Britain -all rights reserved the semiconducting tetragonal Ba2LaTaCu2Os (Murayama et al, 1988), while recent crystal structure determinations of Sr2YMCu207, M=Co, Ga have revealed a complete replacement of square-planar coordinated Cu by tetrahedrally coordinated Co or Ga ions (Huang, Cava, Santoro, Krajewski & Peck, 1992). The present paper reports the preparation of semiconducting oxides Sr2LnTaCu2Os, Ln=Nd, Sm, Eu, Gd, their X-ray powder diffraction characterization and the structure refinement of Sr2SmTaCu208 from X-ray powder diffraction data, as a part of our investigation of the quaternary oxide systems with possible superconducting properties (Bmi~evi6 et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In relation to superconductivity, it is interesting to note that the phases of the TaM 2 RECu 2 O 8−ı (M = Sr, Ba; RE = Pr, Nd, Sm, Eu, Gd) series crystallize in a structure type similar to that of the high-temperature superconductor (HTS) YBa 2 Cu 3 O 7−ı , where Ta 5+ ions are accommodated in the basal plane, whereas the double CuO 2 pyramidal planes are maintained [50][51][52][53]. TaSr 2 (NdCe) 2 Cu 2 O y is the Ta analog of the phase TlBa 2 NdCeCu 2 O 9 [54] and Pb 2 Sr 2 Cu 2 TaO 8 Cl crystallizes in a layered tetragonal structure reminiscent of that of HTS materials [55].…”
Section: Previous Workmentioning
confidence: 99%